Corinthians: Interpreted by Early Christian Commentators, The Church's Bible - Bernas, Casimir (Cistercian studies quarterly, 2006)
The article reviews the book "1 Corinthians: Interpreted by Early Christian Commentators: The Church's Bible," translated and edited by Judith L. Kovacs.